Teaching environmental studies with KUBO robotics - Nikl, Sara; Jančič Hegediš, Polona; Hus, Vlasta (Rethinking childhood II: child and space, 2026)
Computational thinking is defined as a key competence of modern times, as it combines diverse cognitive abilities and skills that help individuals become a successful part of modern society. It is therefore important to start developing it among students from primary school onwards. In this article, we present the activities for developing computational thinking through the content of environmental studies, encompassing objectives from the thematic heading Space in third grade. Through tasks, which were supported with KUBO robotics, students learned how to solve problems, process information systematically, think logically and algorithmically, use abstraction, generalise, cooperate, and above all, it gave them the opportunity to be mentally active through all the learning process. In the empirical portion of the article, we show that despite the limited number of lessons, students have advanced and better understood the basic programming concepts after the activities took place. The activities proved to be interesting as students were drawn to KUBO, which proved to be a useful and applicable tool to teach beginner programming.